On Rivers, Women, and Canoes - Natalie Warren and Phyllis Mauch Messenger (Open Rivers Rethinking Water Place & Community, 2022)
Open Rivers contacted Natalie Warren, author of Hudson Bay Bound: Two Women, One Dog, Two Thousand Miles to the Arctic, to talk about her memoir and the story it chronicles: a river trip by canoe with her best friend, Ann Raiho, from Minneapolis to Hudson Bay.